Peningkatan Kebiasaan Bersih Tangan dan Gigi, Sehat Makanan dan Tidur melalui Tepat Asuh Anak Prasekolah - Wahyuningrum, Eka; Tsiompah, Gregorius; Wibhowo, Christin (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Preschool-aged children need knowledge and support from the family to get used to a healthy lifestyle. Several studies have found that many children don't know how to wash their hands properly, brush their teeth properly, don't like eating vegetables and drinking water and don't get enough sleep. This community service practice aims to familiarize children with healthy lifestyle patterns such as washing their hands and brushing their teeth properly, eating vegetables and drinking water and sleeping healthily. Activities were carried out in Semarang, Central Java in February and March 2023 and were attended by 44 preschool children and 27 parents. Activities carried out include lectures, discussions, questions and answers, singing, demonstrations and simulations with children as well as counseling activities for parents by pediatric nurses, nutritionists and psychologists. The PkM results show that there is an increase in healthy lifestyle habits in hand washing habits, tooth brushing habits, healthy sleeping habits and limiting the use of cellphones. Apart from that, parents stated that the counseling provided was very useful. This PkM activity can provide a reference for methods for improving healthy lifestyles in preschool children.